Measuring occupational stress in emergency departments. (25th October 2022) - McCormick, Ellyse; Devine, Susan; Crilly, Julia; Brough, Paula; Greenslade, Jaimi
Abstract: Objective: EDs are highly demanding workplaces generating considerable potential for occupational stress experiences. Previous research has been limited by a focus on specific aspects of the working environment and studies focussing on a range of variables are needed. The aim of the present study was to describe the perceptions of occupational stress and coping strategies of ED nurses and doctors and the differences between these two groups. Methods: This cross‐sectional study was conducted at a public metropolitan hospital ED in Queensland, Australia. All ED nurses and doctors were invited to participate in an electronic survey containing 13 survey measures and one qualitative question assessing occupational stress and coping experiences. Descriptive statistics were employed to report stressors. Responses to open‐ended questions were thematically analysed. Results: Overall, 104 nurses and 35 doctors responded (55.6% response rate). Nurses reported higher levels of both stress and burnout than doctors. They also reported lower work satisfaction, work engagement, and leadership support than doctors. Compared with doctors, nurses reported significantly higher stress from heavy workload/poor skill mix, high acuity patients, environmental concerns, and inability to provide optimal care. Thematic analysis identified high workload and limited leadership and management support as factors contributing to stress. Coping mechanisms, such as building personal resilience, were most frequently reported. Conclusions: The present study found organisational stressors adversely impact the well‐being of ED nurses and doctors. Organisational‐focused interventions including leadership development, strategic recruitment, adequate staffing and resources may mitigate occupational stress and complement individual coping strategies. Expanding this research to understand broader perspectives and especially the impact of COVID‐19 upon ED workers is recommended.